Salad freak : recipes to feed a healthy obsession - Damuck, Jess (Abrams, 2022)
"Delicious and beautiful recipes from Martha Stewart's personal salad chef and the self-proclaimed "Bob Ross of salads." Offering more than 100 inspired recipes, recipe developer and food stylist Jess Damuck shares her passion for making truly delicious salads. Salad Freak encourages readers to discover and embrace their own salad obsessions. With the right recipes, you will want to eat salad for every meal and never get bored. By playfully combining color, texture, shape, and, of course, flavor, Damuck demonstrates how a little extra effort in the kitchen can be meditative, delicious, and fun. The recipes--such as her Citrus Breakfast Salad; Tea-Smoked Chicken and Bitter Greens Salad; Caesar Salad Pizza Salad; and Roasted Grapes, Ricotta, Croutons, and Endive Salad--are meant to be hearty enough for a meal all year round but versatile enough to be incorporated into a larger menu. For Damuck, the perfect salad balances each bite, with something tart enough to twinge your cheeks, something sweet to balance out the bitter, and something with a little salty crunch to finish. Salad Freak is not just about eating to feel good; it's about confidently combining flavors to create fresh, bright, and satisfying meals that you will want to make again and again."--Publisher's website.